The minimum volume of Consciousness: André du Bouchet’s interoceptive mountain - Salgado Ivanich, Candela (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This article analyzes the organization of consciousness in poetry. We begin by studying certain considerations of contemporary phenomenology and cognitive sciences and the distinction between "subjectivity" and "consciousness" will be elaborated at first. They will be understood respectively, as a first-person perspective centered on the felt experience and as a third person one linked to the objectifiable. A poem written by the French author André du Bouchet, and included in La chaleur vacante, will be analyzed taking into account the use of this subjective level; specifically its interoception —understood in its broadest sense that also includes signs related to movement—, within a landscape consisting of a mountain.